Dinamika Kepemimpinan Pastoral dalam Konteks Manajemen Gereja Modern - Cassandra Laurensia Lolowang; Beni Chandra Purba; Budi Kelana (JUITAK: Jurnal Ilmiah Teologi dan Pendidikan Kristen, 2023)
Abstract This research depicts the results of an in-depth analysis of pastoral leadership dynamics within the context of modern church management through a qualitative literature study approach. The study reveals the importance of integrating solid managerial skills with spiritual dimensions to strengthen church leadership. Research findings affirm that creating a balanced equilibrium between managerial and spiritual aspects is crucial in guiding the church through various challenges in contemporary times, including adapting to evolving technological changes and social dynamics. Furthermore, this research highlights the necessity of adaptation to contextual changes as a critical element in building successful church leadership, wherein church leaders are expected to discern and respond to the dynamics of the external and internal church environment wisely and proactively. In conclusion, this research provides a deeper understanding of how pastoral leadership can be enhanced to manage modern churches more effectively, fulfill the church's mission calling, and serve the community in a more holistic manner.